2017
DOI: 10.1021/acs.est.7b01198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Accessibility of Polycyclic Aromatic Hydrocarbons (PAHs) and Heterocyclic PAHs in Industrially Contaminated Soil after Passive Dosing of a Competitive Sorbate

Abstract: To assess the exposure to polycyclic aromatic hydrocarbons (PAHs) it is important to understand the binding mechanisms between specific soil constituents and the organic pollutant. In this study, sorptive bioaccessibility extraction (SBE) was applied to quantify the accessible PAH fraction in industrially contaminated soil with and without passive dosing of a competitive sorbate. SBE experiments revealed an accessible PAH fraction of 41 ± 1% (∑16 US EPA PAHs + 5 further PAHs). The passive dosing of toluene bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Comparing to industrially contaminated soils, PAH levels were on average 1000 (Bartolomé et al, 2018. ) and 50-400 times (Humel et al, 2017) higher in Swiss soils and landfill-contaminated Austrian soil, respectively (Table 2) than the measured levels in the digested sludge.…”
Section: Figmentioning
confidence: 63%
See 3 more Smart Citations
“…Comparing to industrially contaminated soils, PAH levels were on average 1000 (Bartolomé et al, 2018. ) and 50-400 times (Humel et al, 2017) higher in Swiss soils and landfill-contaminated Austrian soil, respectively (Table 2) than the measured levels in the digested sludge.…”
Section: Figmentioning
confidence: 63%
“…Total concentration data was kindly provided by the WWTPs and is listed in Table 1, and C free was calculated from Eq. (1) using the C silicone data obtained by equilibrium sampling and silicone to water partition coefficients by Humel et al (2017).…”
Section: Determination Of K D Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a common coking by-product, phenol also could promote the solubility of PAHs in aqueous phase [39]. Humel et al [40] found passive dosing of toluene induced an increase in the fraction of accessible PAHs but also enhanced the release rate of PAHs from soil through competitive adsorption, in particular, with more than 4-ring. This study also tested BTEX concentrations in unsaturated zone sampled at C1 and Table 3).…”
Section: The Possible Causes Of Deep Unsaturated Zone Pollutionmentioning
confidence: 99%